2016
DOI: 10.1007/s40751-016-0016-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Complexity to Assess Student Learning from a Robotics-Based Task

Abstract: While robotics is becoming a popular tool to introduce an integrated STEM curriculum into both, elementary and secondary schools, its impact on students' learning remains underexplored. This article addresses the complexity of assessing mathematics learning within a robotics-based task by identifying the different types of knowledge and processes related to digital, mathematical and sociocultural contexts inherent in robotics-based learning. We also studied the ways students interpreted the feedback received w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…Savard and Freiman started their study by pointing out that assessments of children's robotics learning were intrinsically very complicated because children's performances in completing tasks involved different contexts [72]. The authors evaluated and analyzed how 5th and 6th grade children performed robot-tasks by using three different contexts (mathematical, digital, and socio-cultural).…”
Section: Assessment Of Young Children's Robotics Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Savard and Freiman started their study by pointing out that assessments of children's robotics learning were intrinsically very complicated because children's performances in completing tasks involved different contexts [72]. The authors evaluated and analyzed how 5th and 6th grade children performed robot-tasks by using three different contexts (mathematical, digital, and socio-cultural).…”
Section: Assessment Of Young Children's Robotics Learningmentioning
confidence: 99%
“…However, the existing studies relying on the frameworks provided relatively simple descriptions or shallow interpretations of the children's engagement in robotics education. Savard and Freiman suggested that children's robotics learning should be investigated from different perspectives that can capture children's complicated and collective processes [72]. While acknowledging difficulties in examining the details of the children's learning process, Strawhacker and Bers expressed the need for alternative views to provide in-depth qualitative descriptions [53].…”
Section: Dominant Theoretical Frameworkmentioning
confidence: 99%
“…The robotics tools proposed in this framework is LEGO® Mindstorms Education and its compatible software. LEGO® Mindstorms Education is used as it is more user-friendly and is able to serve students' needs from primary schools up to high school levels (Afari & Khine, 2017;Danahy et al, 2014;Savard & Freiman, 2016). eISSN: 2395-6518, Vol 7, No 2, 2019, pp 204-211 https://doi.org/10.18510/hssr.2019.7222…”
Section: Resultsmentioning
confidence: 99%
“…Keane, Keane, and Blicblau stated that appropriate situations need to be created to allow students to develop a mastery of the 4Cs. Students can engage in critical thinking with robots by investigating problems [9].…”
Section: Literature Reviewmentioning
confidence: 99%